WORK-LIFE BALANCE: STRESS AND PERFORMNCE - MARUTHAMUTHU, Dr.M.; CHITRA, S.; PRAMOTHINE, G.; SURENDAR, G. (IJRDO - Journal of Business Management, 2018)
The effect of quality of work-life is one the most important for all human beings and it will lead to the success of any organization for the outcome. Work-life balance policies are the key factors for the success of an organization on employees are balancing their working life as well as personal life also. Hence the researcher focusing on employees are how to consider the importance of their personal situations and organization welfare policies towards effective performance management on balancing their work-life that helps to reduce the stress. Based on the previous studies, organization policies assists to employees for their quality of work-life. This study aims to suggest suitable solutions for overcoming the problems and reduce the stress which leads to encouraging the employee’s better performance for organizational output.